Tree Growth, Foliar Nutrition, and Soil Properties in Mixtures of Lodgepole Pine and Sitka Alder in the Central Interior of British Columbia, Canada: 25-Year Results - Sanborn, Paul; Ott, Peter K. (Frontiers in Forests and Global Change, 2022)
Densities of naturally-regenerated mixtures of lodgepole pine (Pinus contorta Dougl. ex Loud. var. latifolia Engelm.) and Sitka alder (Alnus viridis subsp. sinuata (Regel) Á. Löve & D. Löve) were manipulated in 1995 at a site logged in 1987 in the central interior of British Columbia, Canada. Four levels of alder retention (0, 500, 1000, and 2000 clumps/ha) were combined with a uniform lodgepole pine density of 1000 stems/ha across all treatments. After 25 years, effects of alder retention on lodgepole pine growth consisted of modest reductions in height and diameter increment, and treatment effects on soil nitrogen were confined to the forest floor organic horizons. Nutritional benefits of alder retention for lodgepole pine were not detected after year 6. The operational silvicultural implication of these findings is that only limited intervention to control Sitka alder in similar stands can be justified.